New sources and stability of resistance to aphids in cowpea germplasm across locations in Uganda - Kityo, R.; Odoi, J.B.; Ozimati, A.; Dramadri, I.O.; Agaba, R.; Ongom, P.O.; Nampala, P.; Edema, R.; Karungi, J.; Gibson, P.; Rubaihayo, P.R. (African Journals Online, 2021)
The cowpea aphid (Aphis craccivora Koch) is an economically important pest, whose feeding effects cause stunting, delayed flower initiation and yield reduction in cowpea (Vigna unguiculata L. Walp). Host plant resistance offers an alternative for controlling aphids; while simultaneously reducing reliance on chemical pesticides. The objective of this study was to evaluate a multi-parent advanced generation inter-cross (MAGIC) population of cowpea against aphids, across cowpea growing regions in Uganda. The study was arranged in alpha lattice design, with two replicates in three locations over two seasons (2018B and 2019A). Results revealed significant effects (P<0.001) for the main treatment effects, genotype x location and location x season interaction for both infestation and damage. The genotype x season interaction was significant (P<0.01) for both aphid infestation and damage; while the three-way interaction was only significant (P<0.001) for aphid infestation, but not for damage. The study identified five new resistant and stable genotypes from the MAGIC panel, including MAGIC131, MAGIC-132, MAGIC149, MAGIC170 and MAGIC280; and one resistant parent, SUVITA-2. The study further revealed MAGIC-125, MAGIC-171, MAGIC153, MAGIC-333, MAGIC177, MAGIC-292, MAGIC282, MAGIC249, MAGIC162, SEC 4W * SEC 5T, NAROCOWPEA 4, MAGIC-204, MAGIC-039, MAGIC060, MAGIC-097, NAROCOWPEA 3, MAGIC-233, MAGIC090 and MU 9 to be moderately resistant and high yielding genotypes. The above genotypes are recommended for use in the cowpea breeding programme, to develop improved resistant lines against aphids in Uganda.